Letter from Carl D. Duncan to Patricia Whiting, August 9, 1964 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Carl D. Duncan wrote this letter after spending time pet sitting Patricia Whiting's kitten, Twischen.